Respuesta :

Check the picture below.

bearing in mind that the slope goes by different names

average rate of change

rise over run

rate of change

but is basically the same cat in disguise with different costumes.

[tex]\bf (\stackrel{x_1}{3}~,~\stackrel{y_1}{-2})\qquad (\stackrel{x_2}{6}~,~\stackrel{y_2}{4}) \\\\\\ \stackrel{slope}{m}\implies \cfrac{\stackrel{rise} {\stackrel{y_2}{4}-\stackrel{y1}{(-2)}}}{\underset{run} {\underset{x_2}{6}-\underset{x_1}{3}}}\implies \cfrac{4+2}{3}\implies \cfrac{6}{3}\implies 2[/tex]

Ver imagen jdoe0001
ACCESS MORE